PROFIL PEMBELAJARAN KEANEKARAGAMAN HAYATI DI SMAN 3 BANDUNG - Gusti, Utari Akhir; Hidayat, Topik; Sriyati, Siti (Yayasan Indonesia Bermutu, 2024)
This research aims to provide an overview of biodiversity learning at SMAN 3 Bandung. The research method used is qualitative with a phenomenological design. Data sources come from interviews, observation sheets, and direct observation. This school not only utilizes laboratory and library facilities to provide theoretical knowledge but also maximizes the use of the school garden as a learning space outside the classroom. With this learning, students can observe, document, and appreciate biodiversity directly. Implementation of the Independent Curriculum and the Adiwiyata School concept/green school provides a solid foundation for a sustainable and inclusive learning approach. The research results show that this learning creates students who not only have deep conceptual understanding but also have practical skills and high environmental awareness. SMAN 3 Bandung has succeeded in integrating learning inside and outside the classroom, creating a dynamic and supportive learning environment for students to understand, appreciate and participate in biodiversity conservation. In order to maximize the learning process, it is necessary to assess students' skills and attitudes.